Hubungan Dukungan Suami Dengan Keberhasilan Inisiasi Menyusu Dini Pada Ibu Bersalin Di Puskesmas Wilayah Pesisir - Fahima Ilma Ruhyanudin (CV. SINAR HOWUHOWU, 2025)
Early Initiation of Breastfeeding (EIBF) is a crucial step in improving maternal and neonatal health, particularly within the first hour after birth. This study aims to examine the relationship between husbands’ support and the success of EIBF among postpartum mothers at coastal-area health centers. A quantitative study with a cross-sectional design was conducted on 60 postpartum mothers selected through accidental sampling. Data were collected using a husband-support questionnaire and EIBF observation checklist, and analyzed using the Chi-Square test. The results showed that most husbands provided high levels of support (63.3%), and the majority of mothers successfully performed EIBF (76.7%). Statistical analysis indicated a significant relationship between husbands’ support and EIBF success (p < 0.05). These findings highlight the crucial role of husbands in facilitating successful EIBF, particularly in coastal communities. Strengthening husbands’ involvement in health education is essential to improving EIBF outcomes.